2015
DOI: 10.5812/jjm.8(5)2015.18691
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Epstein-Barr Virus and Human Cytomegalovirus in Chronic Periodontal Patients

Abstract: Background:Although studies focused mainly on the identification of periopathogenic bacteria, recent reports have suggested that various herpes viruses may also be involved in the occurrence and progression of different forms of periodontal diseases.Objectives:This study aimed to compare the prevalence and load of Epstein-Barr Virus (EBV) and Human Cytomegalovirus (HCMV) in subgingival tissue specimens between chronic periodontitis and healthy sites.Patients and Methods:A total of 60 samples from the systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
1
10
0
3
Order By: Relevance
“…Moreover, the EBV virus loads were significantly higher in the AP and CP groups ( P < 0.05). These results are consistent with earlier reports about EBV in periodontitis [ 6 , 9 , 26 , 29 , 30 ]. However, the occurrence of HCMV was 5.3 and 11.9% in the AP and CP groups in this study, lower than what many previous studies have reported [ 31 – 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the EBV virus loads were significantly higher in the AP and CP groups ( P < 0.05). These results are consistent with earlier reports about EBV in periodontitis [ 6 , 9 , 26 , 29 , 30 ]. However, the occurrence of HCMV was 5.3 and 11.9% in the AP and CP groups in this study, lower than what many previous studies have reported [ 31 – 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Gingival sulcus has also been implicated as a favored site for the proliferation of pathogenic viruses like Human papillomavirus and Human herpesviruses 6 and 7 [9][10][11][12]. Symbiotic relationship between gingival microbes could be a potential reason for the high viral proliferation in the gingival sulcus.…”
Section: Letter To Editorsmentioning
confidence: 99%
“…However, in the last decade the presence of herpesviruses has been shown, including HSV1 and 2, EBV, and CMV in periodontal pockets of patients with periodontitis [16][17][18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%